Moral issues in business - Shaw, William H., 1948-; Barry, Vincent E. (Belmont, CA : Thomson Wadsworth, 1998)
The book encourages in-depth thinking about the nature of morality, individual integrity, and responsibility, as well as economic justice, the nature of capitalism and the role of corporations in our society.
Includes bibliographical references and index.
uaj 19/09/2014
Loan
Keywords: Business ethics; Business ethics -- Case studies